ANALISIS IMPLEMENTASI KEBIJAKAN RELOKASI PEDAGANG PELATARAN DI PASAR TRADISIONAL SEMAMPIR KABUPATEN PROBOLINGGO - Rahmatun Ningsih; Suci Megawati (Universitas Negeri Surabaya, 2022)
Zoning traders in traditional market is one of the ways the government to make the market neater. In 2013 Semampir market received a 5 billion rupiah from the assistance fund by East Java Province, which was later by the Regional Government through the authority of Disperindag, was used to relocate the courtyard to the 2 markets, as before the zoning market needs for non-recomoning markets only because they had previously made a non-performing market of selling traffic. This is regulated in the Probolinggo Regency Regulation No.72 of 2018. This research is a descriptive type of research by using a qualitative approach, data source used is a source of primary and secondary data with interactive model data analysis. The results showed that the implementation of the policy of relocated in the market inmpire did not succeed, this is because of the lack of public support such as merchants who are reluctant to occupy the floor building 2 markets. The traders reason that the 2 floor building is not strategic, the difficulty of access to the 2 market, the lack of supporting facilities such as bathrooms, musala, and so on, and the lack of buyer interest in shopping at the floor 2 market. While from the side of the buyer they explain they choose to shop on the ground floor because it is easier to reach and more efficient. The advice given is that a policy perpetrator needs to forum back with traders for berduskusi so that finding an appropriate and profitable solution for both parties then need to add common facilities that traders need on the floor 2 markets. In addition, there also needs to be self-awareness of traders.